Materials of Culture : Approaches to Materials in Cultural Studies - Farahmand, Airin (2023)
While the so-called material turn in the humanities and the social sciences has inspired a vibrant discourse on objects, things, and the concept of materiality in general, less attention has been paid to materials, particularly in cultural studies scholarship. With each of its chapters taking a particular material as its point of departure, this volume offers a palette of fresh approaches to materials within the realm of cultural studies. The contributors call for a materials-based perspective on culture, which has become all the more pertinent in times of climate change, energy crisis, conflict, migration, and the lingering coronavirus pandemic.